2016
DOI: 10.2215/cjn.03990415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Circulating Anti-C3b and Anti-C1q IgG to Lupus Nephritis and Its Flare

Abstract: Background and objectives Autoantibodies to complement C1q (anti-C1q) are associated with the diagnosis of lupus nephritis. In this study, we compare anti-C1q IgG with another complement autoantibody, anti-C3b IgG, as a biomarker of lupus nephritis and lupus nephritis flare.Design, setting, participants, & measurements Our investigation involved the Ohio SLE Study, a prospective observational cohort of patients with recurrently active lupus who were followed bimonthly. Serum anti-C1q and anti-C3b IgG levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 23 publications
1
45
0
3
Order By: Relevance
“…In this regard, autoantibodies to C components that are found in patients with lupus may be important in the development of LN. In a cohort of 114 lupus patients, 23% of patients had autoantibodies to C component C1q and to C3b (43). In these dual-antibody-positive patients who were prospectively followed, anti-C3b and anti-C1q levels tended to increase in the months leading up to renal flare.…”
Section: Pathogenesismentioning
confidence: 99%
“…In this regard, autoantibodies to C components that are found in patients with lupus may be important in the development of LN. In a cohort of 114 lupus patients, 23% of patients had autoantibodies to C component C1q and to C3b (43). In these dual-antibody-positive patients who were prospectively followed, anti-C3b and anti-C1q levels tended to increase in the months leading up to renal flare.…”
Section: Pathogenesismentioning
confidence: 99%
“…Birmingham et al (9) note that, as expected, C3 levels were inversely correlated with anti-C3b antibodies, and they suggest that C3b neoepitopes forming at sites of kidney damage may be driving the formation of anti-C3b antibodies. This study carries several major limitations.…”
mentioning
confidence: 64%
“…In another study, antibodies against C3b, although less frequent than that against C1q, showed a higher specificity for LN, particularly for the prediction of renal flare [127]. Thus, Bb and anti-C3b antibodies appear as new markers for monitoring LN activity [125,127].…”
Section: Lupus Nephritismentioning
confidence: 96%
“…To date, the autoantibodies against C3 and C3b have been reported in LN (Table 2) [126,127]. In the Bulgarian population, anti-C3 antibodies were present in 31% of patients (in 12 of total 39 individuals), and they correlated positively with anti-dsDNA antibodies levels, as well as with the severity of LN.…”
Section: Lupus Nephritismentioning
confidence: 99%